2007
DOI: 10.1111/j.1525-1438.2007.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed genes between high-risk human papillomavirus types in human cervical cancer cells

Abstract: Cervical carcinoma (CC) is one of the most common cancers among women worldwide and the first cause of death among the Mexican female population. Human papillomavirus (HPV) infection is the most important etiologic factor for CC. Of the oncogenic types, HPV16 and HPV18 are found in 60-70% of invasive CCs worldwide. HPV18 appears to be associated with a more aggressive form of cervical neoplasia than HPV16 infection. At present, there are no studies on differentially expressed cellular genes between transformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
0
23
0
3
Order By: Relevance
“…In addition, differentiation-related genes (Nees, Geoghegan et al 2000; Johung, Goodwin et al 2007; Gyongyosi, Szalmas et al 2014), innate immune response genes (Chang and Laimins 2000; Nees, Geoghegan et al 2001; Cortes-Malagon, Bonilla-Delgado et al 2013; Zhou, Zhang et al 2016), DNA damage and stress response genes (Zhou, Zhang et al 2016), and growth factors (Nees, Geoghegan et al 2000) have appeared repeatedly. In studies that take differentiation into account, E7 has been found to have a more profound effect in differentiating cells than in undifferentiated cells (Nees, Geoghegan et al 2001; Vazquez-Ortiz, Garcia et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, differentiation-related genes (Nees, Geoghegan et al 2000; Johung, Goodwin et al 2007; Gyongyosi, Szalmas et al 2014), innate immune response genes (Chang and Laimins 2000; Nees, Geoghegan et al 2001; Cortes-Malagon, Bonilla-Delgado et al 2013; Zhou, Zhang et al 2016), DNA damage and stress response genes (Zhou, Zhang et al 2016), and growth factors (Nees, Geoghegan et al 2000) have appeared repeatedly. In studies that take differentiation into account, E7 has been found to have a more profound effect in differentiating cells than in undifferentiated cells (Nees, Geoghegan et al 2001; Vazquez-Ortiz, Garcia et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…DEDD can attenuate epithelial-mesenchymal transition and acts as an endogenous suppressor of tumor growth and metastasis in human breast cancer [51]. However, overexpression of DEDD was observed in HP16/18 transformed cervical carcinoma cells [52]. Also copy number gain of 1q23.3 which included amplification of DEDD in urothelial tumors was recently described [53] as well as increased DEDD expression in nasopharyngeal carcinoma [54].…”
Section: Discussionmentioning
confidence: 99%
“…Этиологическими факторами возникно-вения РШМ служат вирусы папиллом (HPV) высокого ри-ска, среди которых вирусы HPV16 и HPV18 являются наи-более распространенными и агрессивными [11]. В случае карциномы шейки матки имеются немногочисленные дан-ные об увеличении экспрессии желатиназ А и В в опухоли, а также данные об экспрессии ТИМП-2 [12].…”
Section: архив патологии 5 2015unclassified